The vanishing effect: A film about loss and grief of a mother - Caalangian, Kirk Derick C. (Animo Repository, 2017)
Some studies suggest that parents whose bereavement is more unstable when they lose a child. This production is a short feature film about the grief of losing a loved one, and also about the eventual acceptance of loss as a hallmark of life. The story follows Karmen, a mother who still believes that her missing son, who was presumably a victim in a drowning incident is still alive. She then decides to confront the mother of his son's best friend, who happened to have drowned as well after her son brought him along.